WEWENANG MAHKAMAH AGUNG BERKENAAN DALAM PEMBATALAN PERATURAN DAERAH - Hartono Hartono (Fakultas Hukum Universitas Muhammadiyah Palu, 2018)
Regional regulations are the lowest regulations in the hierarchy of laws and regulations that have the most content material and have a narrow level of flexibility because they must be in line with the laws and regulations above them. This can be understood from the perspective of the Stufenbau des Recht approach expressed by Hans Kelsen, that positive law (regulation) is constructed in stages and in layers, low regulations are sourced from and may not conflict with higher regulations, which we later recognize as the lex principle superior derogat legi inferiori. Judicial review is an impossible choice to correct for mistakes that might occur in a legal product. Even for many people, submitting a Material Test becomes an urgent need. The tendency in this direction can be seen from the desire of some community groups to submit applications and lawsuits in the judicial review which they consider to be controversial to the Supreme Court. Keyword : Supreme Court. Authority. Regional Regulations